Low-temperature synthesized Li4Mn5O12-like cathode with hybrid cation- and anion-redox capacities. Issue 56 (24th June 2019) - Liu, Yang; Liu, Guang; Xu, Hui; Zheng, Yuheng; Huang, Yunhui; Li, Sa; Li, Ju
Abstract : A random Li4 Mn5 O12 -like nanoparticulate cathode demonstrates a high reversible capacity (212 mA h g −1 ) with a hybrid cation-redox capacity (108 mA h g −1 ) and anion-redox capacity (103 mA h g −1 ). Abstract : The Li-rich spinel Li4 Mn5 O12 (Li(Mn5/3 Li1/3 )O4 ) historically only shows a reversible cation-redox reaction, with a theoretical capacity of 135.5 mA h g −1 . However, we found that a simple 400 °C solid-state synthesis method gives a Li4 Mn5 O12 -like nanoparticulate cathode that yields significant reversible hybrid cation- and anion-redox capacities. A high specific capacity of 212 mA h g −1 was achieved. The reversible anion-redox contribution is attributed to the tiny particle size (<10 nm), which facilitates electron tunneling, and a possible random solid-solution in the Li(Mn5/3 Li1/3 )O4 lattice due to the low synthesis temperature.